(untitled) (Journal of Eye Movement Research, 2014)
Research has shown that identifiable visual search patterns characterize skilled performance of anticipation and decision-making tasks in sport. However, to date, the use of experts’ gaze patterns to entrain novices’ performance has been confined to aiming activities. Accordingly, in a first experiment, 40 participants of varying soccer experience viewed static images of oncoming soccer players and attempted to predict the direction in which those players were about to move. Multiple regression analyses showed that the sole predictor of decision-making efficiency was the time taken to initiate a saccade to the ball. In a follow-up experiment, soccer novices undertook the same task as in Experiment 1. Two experimental groups were instructed to either look at the ball, or the player’s head, as quickly as possible; a control group received no instructions. The experimental groups were fastest to make a saccade to the ball or head, respectively, but decision-making efficiency was equivalent across all three groups. The fallibility of a nomothetic approach to training eye movements is discussed.